2017
DOI: 10.1002/eat.22785
|View full text |Cite
|
Sign up to set email alerts
|

Treatment seeking for eating disorders: Results from a nationally representative study

Abstract: To our knowledge, this was the largest study to characterize predictors of treatment seeking in adults with EDs. Results from this study were consistent with existing literature documenting age and sex differences in treatment seeking among adolescents with an ED. Findings suggest a need for improved ED education and outreach-including greater mental health/ED literacy and decreased stigmatization for patients, providers, and the general public-and additional persuasive public-health messages to change communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 56 publications
6
28
0
Order By: Relevance
“…Third, few participants in the sample had current diagnoses of anorexia nervosa or binge‐eating disorder, which may have affected model‐data fit for the latent anorexia nervosa factor. It is important to note, however, that the lifetime prevalence of anorexia nervosa and binge‐eating disorder in the current sample was consistent with prevalence rates from nationally representative data (Bohrer, Carroll, Forbush, & Chen, ). Fourth, although retention was excellent at 6‐month follow‐up, attrition was higher than ideal (43.12%) at 1‐year follow‐up, which may have reduced our ability to predict 1‐year outcomes and stability.…”
Section: Discussionsupporting
confidence: 84%
“…Third, few participants in the sample had current diagnoses of anorexia nervosa or binge‐eating disorder, which may have affected model‐data fit for the latent anorexia nervosa factor. It is important to note, however, that the lifetime prevalence of anorexia nervosa and binge‐eating disorder in the current sample was consistent with prevalence rates from nationally representative data (Bohrer, Carroll, Forbush, & Chen, ). Fourth, although retention was excellent at 6‐month follow‐up, attrition was higher than ideal (43.12%) at 1‐year follow‐up, which may have reduced our ability to predict 1‐year outcomes and stability.…”
Section: Discussionsupporting
confidence: 84%
“…Surveys assessed demographic variables, including gender, age, and race/ethnicity (coded as non‐Hispanic Caucasian vs. ethnic/racial minority for current analyses). Self‐perception of having an ED and treatment‐seeking were assessed with the following “yes” or “no” questions: “Do you believe you have an eating disorder?” and “Have you ever sought formal treatment for an eating disorder?” The use of single‐item assessment replicates prior methods (Bohrer et al, ; Forrest et al, ; Hart et al, ). Consistency of responses to lifetime treatment‐seeking from 2002 to 2012 was acceptable, phi = 0.82, p < .001.…”
Section: Methodsmentioning
confidence: 80%
“…Given the significant levels of distress, impairment, and medical comorbidity associated with EDs (e.g., Arcelus, Mitchell, Wales, & Nielsen, ; Jenkins, Hoste, Meyer, & Blissett, ), understanding factors that influence treatment‐seeking is vital. Recent studies have found that being female increased the likelihood of seeking help for eating or weight problems among adults and adolescents (Bohrer, Carroll, Forbush, & Chen, ; Forrest, Smith, & Swanson, ). The authors suggested that males might be less likely to seek treatment because they are less likely to recognize their ED because they do not match the stereotype of EDs being a female problem.…”
Section: Introductionmentioning
confidence: 99%
“…Help‐seeking intentions also differed across genders and age groups. Previous research has shown women are more likely to seek treatment than men, and positive associations between age and treatment‐seeking (Bohrer, Carroll, Forbush, & Chen, 2017; Fatt et al, in press). However, other work has not found gender to be a primary predictor of help‐seeking (Thapliyal, Mitchison, Mond, & Hay, 2020), suggesting the need for additional research.…”
Section: Discussionmentioning
confidence: 99%